Biotope distribution and ecological groups of the Geometrid moths (Lepidoptera, Geometridae) Northern Tien Shan (Experimental biology, 2016)
In article to be given the result of researches biotope distribution of the geometrid of Northern Tien Shan. As a result of researches uneven distribution of geometrids on biotopes is noted. The greatest number of types of the geometrid meets in the lesolugovykh biotopes (the 49th species). Steppe biotopes occupy 35 species, others 23 species occupy meadow biotopes. 25 species prefer pustyno-steppe biotopes and the smallest quantity of species (4) lives in all biotopes.Depending on the biotope of the geometrid occupied by a look are subdivided into 4 main ecological groups: mesophilic, xerophilic, meso- xerophilic, ubiquists. Mesophilic are presented by 52 species and make 41% of total of fauna. These types prefer forest, river plains and meadow biotopes of different species. 49 (38%) species treat xerophilic which prefer steppe and desert-steppe biotopes. 24 species (18%) - meso- xerophilic the majority from which occupy meadow sites in steppe biotopes, ubiquists the 4th (3%) species live the in all the studied biotopes.
Keywords: Geometridae; Northern Tien Shan; biotopes; ecological groups.